The influences of the Covid-19 pandemic on Swedes’ activity and travel behaviour - Gustafsson, Adam (My University, 2021)
The impact of Covid-19 is determined by, not only the infection and death rate of the actual disease, but the restrictions implemented to halt its spread. The impact these restrictions have is different from country to country, but also when the restrictions are implemented. A summary of Sweden’s restriction timeline has therefore been presented, showcasing that Sweden’s approach increases restrictions throughout the pandemic. A survey was then made, outlining two different pandemic periods, based on the knowledge from the literature study that travel behaviour changes due to restrictions implemented. The survey included questions about mode choice, activity, and travel choice for different purposes, as well as risk perception and health and wealth. The results show to a great extent a decline in public transit usage and frequency of engaging in activities. This is met by an increase in working from home, shopping online, and ordering food. The overall risk perception is very high. This is with regards to the different environments, public transit, public locations, and physical meetings, which serves as the underlying reasons for many of the behavioural changes we have seen in those categories. Understanding what provoke these changes will prove to be valuable when looking at if they continue. Most behaviours show that they will get back to their pre-pandemic figure, like public transit to some extent. Meanwhile the results clearly show that when it comes to working from home, it is expected to continue at a much greater rate than before the pandemic. Overall, the thesis provides important knowledge when it comes to the pandemic and its impact on citizens behaviour.
Keywords: Covid; pandemic; mode choice; survey; Sweden; behaviour change; travel